Description of a new species of Icosta Speiser , 1905 (Diptera: Hippoboscidae) from Southern Vietnam with the updated key to the subgenus Icosta - Aleksandra Yatsuk; Emilia Nartshuk; Andrey Bushuev; Anvar Kerimov; Nguyễn Văn Linh; Oleg Tolstenkov; Alexandr Matyukhin (International Journal for Parasitology: Parasites and Wildlife)
The family Hippoboscidae, commonly known as “louse flies,” comprises pupiparous Diptera that are ectoparasites of birds and mammals, with significant impacts on their hosts and epidemiological importance. The louse fly fauna of Vietnam is relatively understudied compared to other countries in the Southeast Asia region. In this study, we describe a new species of the genus Icosta Speiser, 1905 (Diptera: Hippoboscidae), Icosta korzuni sp. n., collected from the lesser coucal Centropus bengalensis (Gmelin, JF, 1788) in Cat Tien National Park, Vietnam. This new species is distinguished from other Icosta species by the morphology of laterite 3, wing length, arrangement of wing microtrichia, body coloration, and its geographical distribution. Additionally, we provide an updated key to the subgenus Icosta Speiser, 1905.